KUKLUS NIHILIZMO ŽAVESYS - Sodeika, Tomas (Problemos, 2008)
Šerpytytė R. Nihilizmas ir Vakarø filosofija. Vilnius: VU leidykla, 2007. 479 p.ISBN 978-9955-33-035-6Modest Spell of NihilismTomas Sodeika sp;